Gender, Financial Literacy and Pension Savings - Alison Preston; Robert E. Wright (Institute of Labor Economics (IZA), 2022)
Using micro-data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey this paper examines the relationship between the gender gap in financial literacy and the gender gap in pension savings amongst non-retired adults aged 18-64 in 2018. A simple theoretical model is presented. It implies two empirical specifications: a reduced-form specification where the focus is on pension savings and a more structural specification where the focus is on the "pension return" (the ratio of pension savings to cumulative earnings). Oaxaca-Blinder decomposition analysis suggests that around 8.5 per cent of the gender gap in pension savings may be attributed to the gender gap in financial literacy. This finding holds even in the presence of controls for financial risk tolerance. Policy implications and directions for future research are discussed in the paper.
Keywords: H53; J16; J32; 330; pension savings; superannuation; financial literacy; gender gap; decomposition